The Problems of China as a Major Consumer of Energy Resources - Kuznetsova, Natalia Victorovna; Kravchenko, Alla Anatolyevna (International Journal of Energy Economics and Policy, 2019)
The high rates of development in China are increasingly indicated the insufficiency of their own energy resources to maintain the positive dynamics of the growth of the national economy. In the absence of structural changes in the Chinese energy industry, exacerbation of the environmental problem is likely to reduce the inflow of foreign direct investment, on which the PRC economy is also mainly dependent. It is justified that with the rapid growth of the Chinese economy, the problems are growing as the obstacle to the further economic development of the country; it is growing the interdependence of the Chinese and world economies, which is a hidden threat to the stability and well-being of the global economy represented by the PRC. Keywords: GDP growth rates, export, import, living standards, energy resources, energy consumption JEL Classifications: Q4, O3 DOI: https://doi.org/10.32479/ijeep.8478